2017
DOI: 10.1002/2016sw001546
|View full text |Cite
|
Sign up to set email alerts
|

Global modeling of the low‐ and middle‐latitude ionospheric D and lower E regions and implications for HF radio wave absorption

Abstract: We compare D and lower E region ionospheric model calculations driven by the Whole Atmosphere Community Climate Model (WACCM) with a selection of electron density profiles made by sounding rockets over the past 50 years. The WACCM model, in turn, is nudged by winds and temperatures from the Navy Operational Global Atmospheric Prediction System‐Advanced Level Physics High Altitude (NOGAPS‐ALPHA). This nudging has been shown to greatly improve the representation of key neutral constituents, such as nitric oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…The Doppler flash feature can also be analyzed as arising from a change in conductivity of the ionosphere, which leads to a change in phase path of the EM wave. Another study done by Siskind et al (2017) showed that ionospheric absorption peaks at the lower E region and D region of the ionosphere where the ionization maximizes due to enhancement of X-ray and EUV flux. Clearly, the Doppler flash and D and E region absorption phenomenon are related and have similar driving processes.…”
Section: Discussionmentioning
confidence: 98%
“…The Doppler flash feature can also be analyzed as arising from a change in conductivity of the ionosphere, which leads to a change in phase path of the EM wave. Another study done by Siskind et al (2017) showed that ionospheric absorption peaks at the lower E region and D region of the ionosphere where the ionization maximizes due to enhancement of X-ray and EUV flux. Clearly, the Doppler flash and D and E region absorption phenomenon are related and have similar driving processes.…”
Section: Discussionmentioning
confidence: 98%
“…Same as Figure but for midlatitude sounding rocket data taken from Wallops Island, VA. The rocket data are the five profiles listed in Table 1 of Siskind et al (). The VLF data (solid red up to the top of the waveguide; dashed extrapolation above) is taken from the height and steepness values given in Figure 6 of Thomson et al () for a solar zenith angle of 45° (i.e., β = 0.315 km −1 and h=74 km).…”
Section: Comparison Of Two Data Sets With Oasismentioning
confidence: 99%
“…Here we simply note that both the VLF community and the sounding rocket community are interested in the same atmospheric phenomena, which affect the D region. These can include solar variability (Danilov, ; Macotela et al, ; Mechtly, Bowhill, et al, ; Thomson et al, ), planetary waves (related to the winter anomaly discussed in the sounding rocket community; Beynon et al, ; Friedrich et al, ; Garcia et al, ; Pal et al, ; Siskind et al, ; Smith et al, ), and solar perturbations such as flares and eclipses (Bouderba et al, ; Chakraborty et al, ; Clilverd et al, ; Mechtly, Sechrist, et al, ; Mitra & Rowe, ; Singh et al, ). However, despite decades of work measuring the lower ionosphere by these techniques, with only a few exceptions, they typically are not intercompared.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variability in the ionosphere due to forcing from the stratosphere during a sudden stratospheric warming was more accurately reproduced by inclusion of realistic upward propagating GWs. Other examples of WACCM coupling to other models are described by Siskind et al () and Pedatella et al (). Further developments along these lines are being carried out, including assimilation of low‐altitude weather patterns, and validation with observations at low latitudes (McDonald et al, ).…”
Section: Innovative Techniquesmentioning
confidence: 99%